2007
DOI: 10.1681/asn.2006101141
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Ecto-5′-Nucleotidase (CD73) in Renal Ischemia

Abstract: Acute renal failure from ischemia significantly contributes to cardiovascular morbidity and mortality. Extracellular adenosine has been implicated as an anti-inflammatory metabolite particularly during conditions of limited oxygen availability (e.g., ischemia). Because ecto-5-nucleotidase (CD73) is rate limiting for extracellular adenosine generation, this study examined the contribution of CD73-dependent adenosine production to ischemic preconditioning (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
149
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(159 citation statements)
references
References 37 publications
8
149
1
1
Order By: Relevance
“…Although the lymph was derived from patients with different underlying morbidities, these data thus collectively suggest that the intralymphatic lymphocytes can produce substantial levels of anti-inflammatory adenosine when they are exiting the tissues. CD73 regulates the permeability of blood vessels under inflammatory conditions [7,[11][12][13][14][15][16][17]30]. Thus, the blood vasculature of all studied organs in CD73-deficient mice has been shown to be leakier to small molecules in multiple models of ischemiareperfusion injury and LPS-induced inflammation when compared to WT mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the lymph was derived from patients with different underlying morbidities, these data thus collectively suggest that the intralymphatic lymphocytes can produce substantial levels of anti-inflammatory adenosine when they are exiting the tissues. CD73 regulates the permeability of blood vessels under inflammatory conditions [7,[11][12][13][14][15][16][17]30]. Thus, the blood vasculature of all studied organs in CD73-deficient mice has been shown to be leakier to small molecules in multiple models of ischemiareperfusion injury and LPS-induced inflammation when compared to WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…It is synthesized both on blood ECs (BECs) and lymphatic ECs (LECs). The role of CD73 on BECs in controlling vascular permeability and leukocyte trafficking is relatively well understood [11][12][13][14][15][16][17], but the function of lymphatic CD73 remains completely enigmatic. In terms of lymphatic CD73, it is only known that the molecule is expressed on afferent, but not on efferent, LECs, that the expression is higher on LEC than BEC and also that CD73 on LECs is not involved in lymphocyte or DC homing from the periphery into the draining lymph node [18].…”
mentioning
confidence: 99%
“…Bakker and colleagues have reported increased glomerular expression of ecto-5′-nucleotidase in patients with chronic allograft nephropathy [57] and in those with glomerular ischaemia due to malignant hypertension [61]; increased activity of ecto-5′-nucleotidase in fibroblasts in the peritubular space of chronically hypoxic rats has also been reported [62]. A recent detailed study of the importance of ecto-5′-nucleotidase in protecting against renal ischaemia in mice demonstrated that short periods of ischaemic preconditioning caused increases in renal ecto-5′-nucleotidase mRNA and protein, and in renal tissue adenosine [63]. That these events were critical to the protective mechanisms was indicated by the findings that renal function after a subsequent period of renal ischaemia was severely compromised in mice subjected to either pharmacological inhibition of ecto-5′-nucleotidase or deletion of the gene encoding the enzyme [63].…”
Section: Renal Ectonucleotidases Under Pathological Conditionsmentioning
confidence: 99%
“…A recent detailed study of the importance of ecto-5′-nucleotidase in protecting against renal ischaemia in mice demonstrated that short periods of ischaemic preconditioning caused increases in renal ecto-5′-nucleotidase mRNA and protein, and in renal tissue adenosine [63]. That these events were critical to the protective mechanisms was indicated by the findings that renal function after a subsequent period of renal ischaemia was severely compromised in mice subjected to either pharmacological inhibition of ecto-5′-nucleotidase or deletion of the gene encoding the enzyme [63].…”
Section: Renal Ectonucleotidases Under Pathological Conditionsmentioning
confidence: 99%
“…Even though multiple attempts have been undertaken to identify molecular mechanisms that are involved in renal protection by Ischemic preconditioning, the underlying molecular mechanisms are largely unknown 4 . One way to increase the number of organs available for transplant is the improvement of grafts from DCD, as an alternative source to increase organ supply [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%